simplifique a fracao (n)/(n-2)
e (n+3)!/(n-1)!
Soluções para a tarefa
Respondido por
0
Simplificando (n)!/(n-2)!:
(n)!/(n-2)! = n*(n-1)*(n-2)!/(n-2)! = n*(n-1) = n²-n
Simplificando (n+3)!/(n-1)!:
(n+3)!/(n-1)! = (n+3)!/(n+1)*(n+2)*(n+3)! = 1/(n+1)*(n+2) = 1/(n²+2n+n+2) = 1/(n²+3n+2)
Qualquer dúvida, por favor me avise.
Att,
Anderson
(n)!/(n-2)! = n*(n-1)*(n-2)!/(n-2)! = n*(n-1) = n²-n
Simplificando (n+3)!/(n-1)!:
(n+3)!/(n-1)! = (n+3)!/(n+1)*(n+2)*(n+3)! = 1/(n+1)*(n+2) = 1/(n²+2n+n+2) = 1/(n²+3n+2)
Qualquer dúvida, por favor me avise.
Att,
Anderson
Perguntas interessantes
Química,
11 meses atrás
Sociologia,
11 meses atrás
Matemática,
11 meses atrás
Química,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás